Autonomously shaping natural climbing plants: a bio-hybrid approach. Issue 10 (24th October 2018) - Wahby, Mostafa; Heinrich, Mary Katherine; Hofstadler, Daniel Nicolas; Neufeld, Ewald; Kuksin, Igor; Zahadat, Payam; Schmickl, Thomas; Ayres, Phil; Hamann, Heiko
Abstract : Plant growth is a self-organized process incorporating distributed sensing, internal communication and morphology dynamics. We develop a distributed mechatronic system that autonomously interacts with natural climbing plants, steering their behaviours to grow user-defined shapes and patterns. Investigating this bio-hybrid system paves the way towards the development of living adaptive structures and grown building components. In this new application domain, challenges include sensing, actuation and the combination of engineering methods and natural plants in the experimental set-up. By triggering behavioural responses in the plants through light spectra stimuli, we use static mechatronic nodes to grow climbing plants in a user-defined pattern at a two-dimensional plane. The experiments show successful growth over periods up to eight weeks. Results of the stimuli-guided experiments are substantially different from the control experiments. Key limitations are the number of repetitions performed and the scale of the systems tested. Recommended future research would investigate the use of similar bio-hybrids to connect construction elements and grow shapes of larger size.